STUDY ON THE TENDENCY OF ACCRETION AND EROSION IN THE CAN GIO COASTAL ZONE - Bay, Nguyen Thi; Phung, Nguyen Ky (Vietnam Journal of Marine Science and Technology, 2007)
This paper presents the studies on the numerical models to simulate the currents, sediment transport by tide and wind. The results from the models are used to estimate the tendency of accretion and erosion in the Can Gio coastal zone. The basic theory in the numerical models is Reynolds equation system combined with the sediment transport equation and the conservation equation for sediment mass. The computational results of the mass concentration of sediment and the tendency of accretion and erosion in the studied area are in agreement with the satellite photos.